2007
DOI: 10.1152/ajpendo.00373.2006
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-induced sphingosine kinase-1 expression in the rat uterus during pregnancy and signaling consequences

Abstract: Jeng YJ, Suarez VR, Izban MG, Wang HQ, Soloff MS. Progesterone-induced sphingosine kinase-1 expression in the rat uterus during pregnancy and signaling consequences. Am J Physiol Endocrinol Metab 292: E1110 -E1121, 2007. First published December 12, 2006; doi:10.1152/ajpendo.00373.2006.-Sphingosine 1-phosphate (Sph-1-P), a product of sphingomyelin metabolism, can act via a family of cognate G protein-coupled receptors or as an intracellular second messenger for agonists acting through their membrane receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 55 publications
3
12
2
1
Order By: Relevance
“…A recent study showed that in uterus, SphK1 mRNA and protein increased at late pregnancy (23). However, no significant pregnancy-related changes in SphK2 mRNA levels were observed in this study (23). By contrast, we demonstrated that in myometrial tissues, not only the levels of SphK2 protein, but also its activity, increased at the end of gestation.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…A recent study showed that in uterus, SphK1 mRNA and protein increased at late pregnancy (23). However, no significant pregnancy-related changes in SphK2 mRNA levels were observed in this study (23). By contrast, we demonstrated that in myometrial tissues, not only the levels of SphK2 protein, but also its activity, increased at the end of gestation.…”
Section: Discussioncontrasting
confidence: 92%
“…These findings suggested that SphK1/2 protein synthesis may be similarly controlled in the myometrium at the end of gestation. A recent study showed that in uterus, SphK1 mRNA and protein increased at late pregnancy (23). However, no significant pregnancy-related changes in SphK2 mRNA levels were observed in this study (23).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, we recently reported that in ELT3 cells, SphK1 and S1P exerted an antiapoptotic effect (4) and that exogenous S1P stimulated DNA synthesis (unpublished results). In agreement with these observations, Jeng et al (45) found that overexpression of SphK1 in ELT3 cells increased cell proliferation. In light of these data, it became possible to postulate that the SphK1/S1P pathway may be one mechanism by which endogenous PA contributes to ET-1-mediated ERK 1/2 activation and cell proliferation in ELT3 cells.…”
Section: Discussionsupporting
confidence: 55%